Surface acoustic cavitation understood via nanosecond electrochemistry. 2. The motion of acoustic bubbles - Maisonhaute, E; Brookes, B; Compton, R (2002)
Acoustic cavitation considerably enhances the mass transport toward a surface. When suitably fast electrochemical equipment is used, periodic peak currents can be observed. Previous observations attributed these peaks to diffusion inside a thin liquid layer present between the electrode and the bubble (Maisonhaute, E.; White, P.C.; Compton, R.G. J. Phys. Chem. B 2001, 105, 12087-12091). This paper provides a semiquantitative model for explaining the bubble behavior, leading to an estimation of the diffusion layer thickness as well as the time during which the bubble "discovers" the electrode. Layer thicknesses ranging from 25 nm for very high acoustic pressures up to ca. 60 nm for smaller ones are found. Collapse velocities are estimated to be more than hundreds meters per second. Moreover, between two collapses, a slow bubble movement apart from the surface is evidenced. The force balance responsible for the collapse is reexamined and the viscosity constraint found to be an important parameter in explaining the global behavior.